2019
DOI: 10.1111/tri.13443
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk for kidney donors with hypertension at donation – a retrospective cohort study

Abstract: In the general population, small increases in blood pressure are associated with increased mortality. In kidney donors this association is less certain. We therefore assessed long-term overall and cardiovascular mortality in donors who were hypertensive at the time of donation compared with normotensive donors. Hypertension was defined as blood pressure >140/90 mmHg or use of antihypertensive drugs. Adequate records available in 2131 donors revealed that 140 were hypertensive and 1991 were normotensive. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…On other hand, in large general population, the connection between a decrease eGFR and raised relative hazard for different destinations areevidently identified. Even though the above study identified an increased rate of cardiac fatality risk in 10 donors during an 8.5-year follow-up span, HTN at the time of donating kidney was not statistically correlated with cardiovascular complications and or death in our study.We may hypothesize that the link between systolic BP and raises the cardiac complication risk is difficult to detect incomparatively stable subjects of live kidney donors, predominantly in small population cohort with undersized follow up periods 10 .Donor candidates with managed hypertension should be evaluated and cared for according to the 2017 KDIGO Clinical Practice Recommendation on the Assessment and Care of Live Kidney Donors suggest if there is no proof of target organ injury, they could be eligible for donation 11 . However, our findings and those of other researchers show that, regardless of other risk factors, HTN at the time of donating kidney is linked to a lowereGFR after donation.…”
Section: Discussionmentioning
confidence: 99%
“…On other hand, in large general population, the connection between a decrease eGFR and raised relative hazard for different destinations areevidently identified. Even though the above study identified an increased rate of cardiac fatality risk in 10 donors during an 8.5-year follow-up span, HTN at the time of donating kidney was not statistically correlated with cardiovascular complications and or death in our study.We may hypothesize that the link between systolic BP and raises the cardiac complication risk is difficult to detect incomparatively stable subjects of live kidney donors, predominantly in small population cohort with undersized follow up periods 10 .Donor candidates with managed hypertension should be evaluated and cared for according to the 2017 KDIGO Clinical Practice Recommendation on the Assessment and Care of Live Kidney Donors suggest if there is no proof of target organ injury, they could be eligible for donation 11 . However, our findings and those of other researchers show that, regardless of other risk factors, HTN at the time of donating kidney is linked to a lowereGFR after donation.…”
Section: Discussionmentioning
confidence: 99%
“…We investigate the past medical history, previous hospitalisation, and regular medications. Hypertension controlled with up to two medications is not a contraindication according to the British Transplant Society guidelines [26]; moreover, there is evidence that this does not affect long-term overall or cardiovascular mortality [27]. Proteinuria, diabetes, angina/heart disease, stroke, severe pulmonary disease, kidney stone (or other kidney disease), blood disorders, sickle cell disease, or active cancer are contraindications to donate.…”
Section: Discussionmentioning
confidence: 99%
“…In the registry analysis from Haugen et al [4], POD occurred in 42 patients (4.7%): 8 (19%) characterised by the hypoactive subtype, 7 (16.7%) by the hyperactive one and 27 (64.3%) with both aspects. The cumulative incidence ranged from 2% (18-48 years old patients) to 13.8% (≥75 years).…”
mentioning
confidence: 98%
“…Table 1 summarises the results of the four studies analysed [4][5][6][7] in our SR: clinical trials, prospective and retrospective reports with >10 patients, from 01 January 1955 to 13 December 2020 with "kidney transplant" AND "postoperative delirium" or "renal transplant" AND "postoperative delirium" as keywords. In the 128.258 adult KT patients identified in total, mean age was 50.9 years.…”
mentioning
confidence: 99%